Evaluation of noni extract on mouse macrophages for its immune-enhancer property - Mangesh Mankar,; Sameena Akhtar,; C S Senthil Kumar,; S Ravi,; Sunil Kumar,; Ragini Gothlwal,; Narayanan Ganesh, (International Journal of Phytomedicine, 2013)
Morinda citrifolia L. has been used in a traditional Polynesian medicine for over 2000 years. The fruit are consumed by various communities all over the world. Due to its nutritional value, it has received an increasing importance. The present study analyzed the phagocytic property of Morinda citrifolia L (Noni drug). The BD dose (0.266 mg / 25 gm mice) of Noni drug was used to test the immunoenhancer property on Swiss albino mice. Animals were divided in to 4 groups of both either sex. Test group animals in each molecular weight were treated with OD and BD dose of noni orally, control group animal were treated with plain drinking water and standard control animal were treated with Cyclosporine A according mice weight. The BD treated animal exhibited 77.89% phagocytic activity when compared with control which exhibited 27.23%, OD group animal 47.77% and standard group animal 18.75%.